PENGARUH KOMUNIKASI POLITIK APARATUR SIPIL NEGARA TERHADAP PELAYANAN PUBLIK - Ika Widiastuti (Yayasan Nusantara Hasana Berdikari, 2023)
Harmonious political communication, carried out by government officials and the community, can improve public services. The community can participate in local government policies on political communication. This study uses quantitative methods using simple linear regression analysis. sample determination using purposive sampling technique while data analysis using SPSS. The result of the research is that political communication has a significant effect on public services.